Effects of spacing distance and fuel mass thickness on combustion and flame merging characteristics of two-line pool fires. (October 2022) - Huang, Xinjie; Hu, Junjie; Zhou, Zhijie; Shao, Yu; Zhu, Haowei; Zhang, Yang; Liu, Chunlin; Wu, Yuxin
Abstract: Flame merging of line fires is very complex with the interaction of fire dynamics and fluid flow et al., which will often generate different burning behaviors. In this paper, the effects of spacing distance and fuel mass thickness on the combustion and flame merging characteristics of two n-heptane line pool fires were studied. With the dimensionless liquid fuel height H* (Fuel height/Groove depth) increase, the probability of flame merging, and the temperature of the additional air entrainment region gradually increase. The merging flame will change from no hole, with hole, hole increased to hole open stage with spacing distance increase. It is interesting to find that, the mass loss rate of each line fire is less than that of a single line fire burning alone, and the closer the distance is, the smaller the value is. Meanwhile, for a single or double linear fires at H* = 3/4, the mass loss rate is the greatest. By establishing a heat transfer model, it is demonstrated that at H* = 3/4, the ullage of the groove has a stabilizing effect on the flame, which makes the flame height the largest. The results of this study will enhance the understanding of the flame merging of line fires with different fuel masses.